Toll‐like receptor 9 mediates invasion and predicts prognosis in squamous cell carcinoma of the mobile tongue. (23rd October 2014) - Kauppila, Joonas H.; Korvala, Johanna; Siirilä, Kristiina; Manni, Marika; Mäkinen, Laura K.; Hagström, Jaana; Atula, Timo; Haglund, Caj; Selander, Katri S.; Saarnio, Juha; Karttunen, Tuomo J.; Lehenkari, Petri P.; et al.
<x xml:space="preserve">Abstract</x> Background Toll‐like receptor 9 (TLR9) is a cellular receptor, which recognizes bacterial and host‐derived DNA. Stimulation of TLR9 induces cellular invasion via matrix metalloproteinase 13 (MMP‐13). The aim of this study was to evaluate the role of TLR9 in invasion of oral tongue squamous cell carcinoma (OTSCC). Methods The effects of TLR9 ligands on oral squamous cell carcinoma cell lines were studied with invasion and migration assays, as well as in a myoma organotypic model. Results The TLR9 ligand, CpG‐ODN, increased invasion and migration in OTSCC lines. These effects were reduced by TLR9 siRNA or inhibition with TLR9 antibodies. Immunohistochemical analysis of tissues from 195 patients with OTSCC revealed that TLR9 was expressed in 181/195 carcinomas. The expression of TLR9 was higher in the malignant cells than in the normal epithelium. High TLR9 expression was associated with high MMP‐13 expression and poor differentiation. High TLR9 expression was also identified as an independent predictor of poor prognosis (HR 1.810, 95% CI [1.053–3.112]). Conclusion Toll‐like receptor 9 mediates OTSCC invasion and migration in vitro and is an independent prognostic factor of OTSCC. Inhibition of TLR9 may be a novel therapeutic opportunity in oral cancer.